Effect of severe thermo-oxidative aging on the mechanical behavior and fatigue durability of short glass fiber reinforced PA6/6.6. (January 2023) - Alexis, Florent; Castagnet, Sylvie; Nadot-Martin, Carole; Robert, Gilles; Havet, Peggy
Highlights: Higher fiber concentration tends to reduce thermal aging degradation. Fiber orientations have an impact on the aging process and fatigue lifetime decline. Fatigue initiation approach is still valid for aged specimens. Best pre-aging criteria remain the best post-aging; preserved unification abilities. Abstract: The work deals with the fatigue lifetime estimation of Short Fiber Reinforced Thermoplastics (SFRP), with a focus on conjugated effects of thermal aging. Two materials containing 35% (V35) and 50% (V50) weight ratio of short glass fibers were aged for 500 h at 200°C in air and compared to the same materials in a Dry-As-Molded (DAM) state. Monotonic and fatigue tests were performed in samples machined out of injected plates and cut along three different orientations to the injection one (0°, 45°, 90°) in order to capture the anisotropy of the skin-core microstructure, classical in injected SFRP. Monotonic tensile tests evidenced the stiffening and embrittlement of the Polyamide matrix reported in the literature, nevertheless with an acuity depending on the matrix ratio and fiber orientation. Stress-controlled fatigue tests were performed at constant amplitude, frequency (10 Hz), temperature (200°C) and stress ratio R = 0.1. The fatigue curves of V35 are more affected by aging than those of the V50 material. The combined results from the mean strain evolutions and SEM observations confirmed that the initiation approach for fatigue lifetime estimation was still valid in aged composites. Several fatigue criteria, among the most recently reported in the literature, were evaluated from this database. The effect of aging on the cyclic evolution of the different Fatigue Indicator Parameters (FIP) involved in the criteria was analyzed preliminarily. For the present fatigue conditions, the best criteria for unaged materials (i.e cyclic creep energy-based ones) were shown to still be the best for aged materials. Finally, the ability to predict fatigue lifetime for aged composites from the identification of the fatigue criterion in the unaged state was evaluated.